Rural and Urban Trends in Family and Intimate Partner Homicide in the United States, 1980-1999 - Gallup-Black, Adria ([Verlag nicht ermittelbar], 2005)
This research project examined rural and urban trends in family and intimate partner homicide for the 20-year period from 1980 through 1999. The construct of place served as a backdrop against which changes in trends in family/partner homicide were tracked, and against which various independent measures that purportedly explain variation in the rates were tested. The project merged data from several sources. The offender data file from the Federal Bureau of Investigation's (FBI) Supplementary Homicide Report (SHR) series for 1980 through 1999 was the primary data source. Data for arrests for violent crime, drug, and alcohol-related offenses were obtained from the FBI Report A Arrest File. Population, population density, and race (and racial segregation) data from the decennial U.S. Census for 1980, 1990, and 2000 were also obtained. Data on hospitals, educational attainment, unemployment, and per capita income were obtained from the 2002 Area Resource File (ARF). The total number of proprietors (farm and non-farm) in the United States by state and county for each year were provided by the Regional Economic Profiles data. The project's population and proximity indicator used four categories: metropolitan, nonmetropolitan populations adjacent to a metropolitan area, nonmetropolitan populations not adjacent to a metropolitan area, and rural. Data include homicide rates for 1980 through 1999 for intimate partner homicide, family homicide, all other homicide, and all homicide. Additional variables are included as measures of community socioeconomic distress, such as residential overcrowding, isolation, traditionalist views of women and family, lack of access to health care, and substance abuse. Five-year averages are included for each of the rates and measures listed above.